PENGEMBANGAN ALAT PERMAINAN EDUKATIF “FEED THE CHICKEN” SEBAGAI UPAYA BIMBINGAN DAN PENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA DINI - Yuni Sarah; Hasibuan, Liliana (Universitas Islam Ahmad Dahlan, 2026)
This study aims to develop an educational game tool, “Feed the Chicken,” to enhance the cognitive abilities of early childhood children. The development process follows a research and development (R&D) approach, including needs analysis, design, prototyping, testing, revision, and evaluation. The game is designed to stimulate memory, attention, decision-making, and problem-solving skills through interactive and enjoyable activities suitable for children aged 4–6 years. Validation by experts and field testing in early childhood education settings ensure the game is effective, practical, and engaging. The study emphasizes the importance of local adaptation, teacher and parental involvement, and scalable design to accommodate various cognitive levels. Findings indicate that children show improved cognitive performance, higher engagement, and increased motivation during learning activities using the game. The “Feed the Chicken” tool demonstrates that educational games can serve as an innovative media to support early childhood cognitive development while providing enjoyable and meaningful learning experiences.